2021
DOI: 10.1007/s40263-021-00815-y
|View full text |Cite|
|
Sign up to set email alerts
|

Real-World Evidence of the Clinical and Economic Impact of Long-Acting Injectable Versus Oral Antipsychotics Among Patients with Schizophrenia in the United States: A Systematic Review and Meta-Analysis

Abstract: Background Long-acting injectable (LAI) antipsychotics, compared with oral antipsychotics (OA), have been found to significantly improve patient outcomes, including reduced hospitalizations and emergency room (ER) admissions and increased medication adherence among adult patients with schizophrenia. In turn, the clinical benefits achieved may translate into lower economic burden. Real-world evidence of the comparative effectiveness of LAI is needed to understand the potential benefits of LAI outside of the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 63 publications
2
61
1
Order By: Relevance
“…Particle size (Y1) = +49.91 A + 42.96 B + 88.44 C − 30.24 AB − 68.56 AC − 80.96 BC (1) The data in Table S2A and the associated ANOVA findings (Table S3A) show that the regression coefficients of the tested CPPs all had p values < 0.05, suggesting that they have a significant influence on PM particle size.…”
Section: Influence Of Different Critical Process Variables On Particl...mentioning
confidence: 99%
See 1 more Smart Citation
“…Particle size (Y1) = +49.91 A + 42.96 B + 88.44 C − 30.24 AB − 68.56 AC − 80.96 BC (1) The data in Table S2A and the associated ANOVA findings (Table S3A) show that the regression coefficients of the tested CPPs all had p values < 0.05, suggesting that they have a significant influence on PM particle size.…”
Section: Influence Of Different Critical Process Variables On Particl...mentioning
confidence: 99%
“…Schizophrenia is a mental disorder characterized by hallucinations, alterations in cognition, behavior, emotion, and disorganized speech that severely cause distress and daily functional impairment [1,2]. Approximately 23 million people worldwide are suffering from schizophrenia, 1% of whom are in adolescence or early adulthood [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The PRIDE study was a real-world study for superiority of paliperidone to oral antipsychotics in schizophrenia that led to label expansion by FDA in 2018 [33]. A metanalysis of retrospective and pragmatic real-world studies reported a discernible benefit of long-acting injectable (LAI) antipsychotics over oral antipsychotics in Schizophrenia in terms of cost-effective and sustained patient outcomes [34].…”
Section: Pragmatic Clinical Trialsmentioning
confidence: 99%
“…Fourth, LAIs significantly reduce the rate of hospitalization, according to a recent meta-analysis [ 10 ]. Thus, LAIs are not only clinically effective but also reduce medical costs, as shown in a meta-analysis [ 11 ]. Another benefit of LAIs is the lower risk of being arrested or incarcerated in patients treated with LAIs compared to OAPs, in a randomized review board-blinded study [ 12 ].…”
Section: Introductionmentioning
confidence: 99%